2020
DOI: 10.3390/nu13010130
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Barley β-Glucan Affects Glucose and Lipid Metabolism by Prebiotic Effects

Abstract: We investigated the effect of low molecular weight barley β-glucan (LMW-BG) on cecal fermentation, glucose, and lipid metabolism through comparisons to high molecular weight β-glucan (HMW-BG). C57BL/6J male mice were fed a moderate-fat diet for 61 days. LMW-BG or HMW-BG was added to the diet corresponding to 4% β-glucan. We measured the apparent absorption of fat, serum biomarkers, the expression levels of genes involved in glucose and lipid metabolism in the liver and ileum, and bacterial counts of the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…Taking into account the rates of change of TBF%, the greater reduction in TBF% was observed with 5g -70% BG that was significantly different than 3g -70% BG according to the Bonferroni paired test, which may be related to the low molecular weight BG being more fermentable than the 35% BG. In a recent study carried out in mice, 53 changes in abdominal fat depots, serum cholesterol and leptin concentrations in the group of animals that consumed the low molecular weight BG were related to BG prebiotic effects, as almost 100% was fermented and caecal bacterial counts of Bifidobacterium and Bacteroides were significantly raised, increasing caecal contents of acetic and propionic acids. In contrast, in mice fed the high molecular weight BG the positive changes in abdominal fat, serum cholesterol and leptin concentrations observed were related to the inhibition of nutrient absorption due to high viscosity in the digestive tract.…”
Section: Food and Function Accepted Manuscriptmentioning
confidence: 95%
See 1 more Smart Citation
“…Taking into account the rates of change of TBF%, the greater reduction in TBF% was observed with 5g -70% BG that was significantly different than 3g -70% BG according to the Bonferroni paired test, which may be related to the low molecular weight BG being more fermentable than the 35% BG. In a recent study carried out in mice, 53 changes in abdominal fat depots, serum cholesterol and leptin concentrations in the group of animals that consumed the low molecular weight BG were related to BG prebiotic effects, as almost 100% was fermented and caecal bacterial counts of Bifidobacterium and Bacteroides were significantly raised, increasing caecal contents of acetic and propionic acids. In contrast, in mice fed the high molecular weight BG the positive changes in abdominal fat, serum cholesterol and leptin concentrations observed were related to the inhibition of nutrient absorption due to high viscosity in the digestive tract.…”
Section: Food and Function Accepted Manuscriptmentioning
confidence: 95%
“…Two human intervention studies assessed the effects of oat or barley products on appetite ratings (including satiety) after eating the test food on a single occasion, 56,57 although only the former reported the effects on subsequent energy intake. 53 It is noteworthy that these studies focused on single meals and not on the effects of the sustained consumption of fibre rich products, such as in this study that approached the influence on appetite as well as on subjective digestive function related to consuming twice a day the nutraceuticals containing BG for six weeks. This is an important issue, as effects on satiety may continue up to several hours and reduce energy intake at the next meal or, if sustained across the day, it may lead to a greater reduction in food intake and thus body weight.…”
Section: Food and Function Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies have shown that barley β-glucan ( 33 ) and polysaccharides, such as galacto-oligosaccharides ( 34 ), arabino-oligosaccharides ( 35 ), and inulin ( 36 ) can be widely utilized as energy sources, with acetic acid as the primary metabolite. Several studies with humans and animals investigating the effects of prebiotics reported that Bifidobacterium and acetic acid increased in the feces or cecum as a result of prebiotics ( 37 , 38 ). Therefore, it seems reasonable that the gut without dyslipidemia was enriched in Bifidobacterium , regardless of barley intake in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-glucan (BG) is a naturally derived polysaccharide composed of soluble dietary fibers with three β (1–4) and one β-(1–3) glycosidic-linked glucose molecules in a repeating unit (RU) . Due to its diverse physiological functions, bioactive (biocompatibility and biodegradability) properties, and health benefits, BG has been widely exploited in pharmacology and targeted drug delivery. , BG has shown to have an affirmative action in controlling glucose levels and serum cholesterol and attenuating coronary heart disease conditions. A significant number of clinical studies and consequent meta-analysis have been carried out that strongly support oat/barley BG’s efficiencies in lowering LDL (low-density lipoprotein) cholesterol in the human body. , Consequently, leading regulatory agencies like the United States FDA have issued the health benefits of oat/barley BG and its functionality in mitigating blood lipid concentrations and improving conditions responsible for metabolic syndrome. , It has been reported that the BG polymer utilizes its viscosity property and gel-forming ability to form droplets with fat molecules . Along the same line, BG fibers help increase the viscosity and structural rigidity of the lipid droplets, which further delays the lipid digestion process by inhibiting the lipase enzyme activity in the small intestine. , A recent study by Thandapilly et al demonstrated that BG-mediated hypocholesterolemia largely depends on the molecular weight (MW) of the BG and occurs through an increase in the bile acid excretion and short-chain fatty acids in the intestine .…”
Section: Introductionmentioning
confidence: 99%